The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Psykhe (Santiago) 2019
DOI: 10.7764/psykhe.28.2.1505
|View full text |Cite
|
Sign up to set email alerts
|

"No, We're Not Culturally Ready for That Yet": Chilean Heterosexual Women's Discourses on Lesbian and Gay Parenting

Abstract: This study examined Chilean heterosexual women's discourses concerning lesbian and gay (LG) parenting following a social constructionist perspective. Data from a convenience sample of 15 first-year psychology female students attending an evening university program in Concepción, Chile, were collected through 3 focus groups. Findings through a thematic analysis indicated that the major concern participants reported was that children of same-gender couples would be discriminated, because of their parents' sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Further factors important in promoting Chilean social awareness and acceptance of lesbianism were the high-profile recognition of Nobel prize winner Gabriela Mistral's relationship with Doris Palma and also the media coverage of Judge Karen Atala's successful custody battle through the courts. Nevertheless, many Chilean people still see lesbianism as incompatible with motherhood and consider that it is not normal for children to be growing up in a lesbian-led household (Herrera, 2009;Figueroa and Tasker, 2019).…”
Section: The Chilean Sociolegal Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Further factors important in promoting Chilean social awareness and acceptance of lesbianism were the high-profile recognition of Nobel prize winner Gabriela Mistral's relationship with Doris Palma and also the media coverage of Judge Karen Atala's successful custody battle through the courts. Nevertheless, many Chilean people still see lesbianism as incompatible with motherhood and consider that it is not normal for children to be growing up in a lesbian-led household (Herrera, 2009;Figueroa and Tasker, 2019).…”
Section: The Chilean Sociolegal Contextmentioning
confidence: 99%
“…The present study was conducted with LM who, at the time the study, were all living in Chile, a Latino country with a strongly Christian (mainly Catholic) religious heritage. For example, a study that explored discourses concerning lesbian and gay (LG) parenting in Chile indicated that some Christian heterosexual women expressed the view point that having LG parents could disrupt a child's gender and sexual identity development while other heterosexual women suggested 'no we're not culturally ready for that yet' (Figueroa and Tasker, 2019).…”
Section: Introductionmentioning
confidence: 99%